Community Forest Scheme: Measuring Impact in Livelihood Case Study Lombok Tengah Regency, West Nusa Tenggara Province - Eny Widiya Astuti; Aceng Hidayat; Dodik Ridho Nurrochmat (Institut Pertanian Bogor (IPB University), 2020)
Community forest (Hutan Kemasyarakatan/HKm) is one of the social forestry scheme policies stipulated by the Indonesian government to give partial rights to the community to be able to manage the state forest area. This scheme has implemented for more than ten years, and that includes areas in Lombok Tengah Regency. This research aims to analyze the impact of social forestry scheme policies on the economy of communities around forests and conducted in May–August 2019. By the HKm scheme, the community can manage up to 0.5 ha forest area per person and expected to increase livelihood benefits as well as improve conservation outcomes such as decreasing illegal logging and planting more trees. Based on the study conducted, the community has experienced an increase in livelihoods as well as improvements in environmental conditions. Indicator used in measuring community welfare is per capita income, which noted in the study area is IDR3,609,603 annually and inequality (Gini coefficient), which noted less than 0.4 or in the 'low' category. This study shows that the Gini coefficient in the research location is high (0.530). When compared, the income gap in the group of respondents who got the HKm program was better than the group of respondents who did not. The Gini coefficient data shows that the HKm program quite succeeds in target to increase livelihood benefits. The HKm program expected to improve the level of income inequality (Gini coefficient) from 0.483 (HKm) compared to 0.566 (non-HKm). These findings are important messages to further the HKm scheme policies.